Gender-konstruksies in die afrikaanse letterkunde : 'n ondersoek in kultuurstudies, litterêre teorie en kreatiewe skryfwerk - Hambidge, Joan (African Languages and Literatures, 2019)
This thesis argues that gender is a construct or a choice. The different gender positions (feminisms, masculinities, homosexualities et al.) are read against modem literary theory. When applicable a particular theory is tested from a creative perspective. The outset of the thesis is metafictional and selfreflexive seeing that the thesis sets out to "test" theory and to undermine the stereotypical notion that theory and creative writing belong to different disciplines. Thus the reader is presented with a deconstructive thesis or a text which challenges the notion of modem theory and cultural studies. Representation, clothes, primordiality, humour, the internet, the media, films, "pulp" fiction and "high" literature are analysed and blended in this thesis to comment on the developments in modem literary theory: structuralism to post structuralism. The influence of the internet is discussed in a chapter. The thesis comments on the value of inter-disciplinary work and programmes. Psychoanalytic and (post)structuralist theories are blended with creative texts to undermine the notion that gender is a mere biological or given position. The conventional boundaries of a literary thesis is thus challenged and the thesis argues that critical texts and creative texts rely on this interactive reading.